Formulation, Optimization And In Vitro Characterization Of Mucoadhesive Microparticle - Parmar, Harshad (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Mucoadhesive microparticle of Itopride HCl was design in order to obtain a unique drug delivery system which would remain in the stomach and prolong the residence time at the absorption site by intimate contact with the mucus layer thereby increase bioavailability, reduce the frequency of dose administration and also to prolong the drug release. The mucoadhesive microparticles were prepared by Orifice ionic gelation method using sodium alginate in combination with carbopol 934 and HPMC K15. Entrapment efficiency was in the range of 41.32 to 81.68 %. Microparticle exhibited good mucoadhesive property in the in vitro wash off test and revealed that Carbopol 934 had greater mucoadhesive strength than that of HPMC K15. Itopride HCl release from this mucoadhesive microparticle was slow and showed sustained release. SEM study revealed that microparticles were discrete, spherical and free flowing. Stability study of optimized batch was carried out and drug content found was retained with permissible limits and there was no significant difference in the drug content.